2007
DOI: 10.1097/mpa.0b013e318033f9f4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Clonal Colony-Forming Assay for Propagation of Pancreatic Cancer Cells With Stem Cell Properties

Abstract: A subpopulation of PANC-1 cells can propagate to form spheres with properties of stem cells in this assay; enough of these cells can be obtained for further study. Considering the overexpression of mRNA, it was tentatively suggested that LY6E, TACSTD1, and CD44 proteins may act as surface markers for sorting pancreatic cancer stem cells with fluorescence-activated cell sorter/magnetic-activated cell sorter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 26 publications
2
98
0
Order By: Relevance
“…39,64 They can propagate to form clonal growth and mammospheres in vitro that are surrogate detection methods for cancer stem cell properties. 7,24,65,66 Our studies found that ASA significantly reduced clonal growth (Figure 3), blocked self-renewal of BTICs (Figure 4), reprogrammed the mesenchymal to epithelial transition ( Figures 5 and 6), and reduced aggressive behavior of residual BC cells. However, the precise mechanisms of ASA action on regulation of pathobiological behavior of BTICs/BCSCs are still unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…39,64 They can propagate to form clonal growth and mammospheres in vitro that are surrogate detection methods for cancer stem cell properties. 7,24,65,66 Our studies found that ASA significantly reduced clonal growth (Figure 3), blocked self-renewal of BTICs (Figure 4), reprogrammed the mesenchymal to epithelial transition ( Figures 5 and 6), and reduced aggressive behavior of residual BC cells. However, the precise mechanisms of ASA action on regulation of pathobiological behavior of BTICs/BCSCs are still unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of CSCs, or tumor-initiating cells, was first reported by Lapidot and colleagues (93). Since then, CSCs have been identified in numerous solid tumors, including breast, colon, endometrial, pancreas, prostate, ovary, and brain tumors (94)(95)(96)(97)(98)(99)(100)(101)(102). High tumorigenicity was shown in CSCs.…”
Section: Emt Met and Cancer Stem Cellsmentioning
confidence: 99%
“…In the latter assay, the CSCs of PDAC cells form floating colonies when cultivated in ultra-low-attachment dishes (9)(10)(11) (12). In a previous study, we reported that nestin, a pancreatic CSC marker, is more highly expressed in the spheres of three PDAC cell lines than in nonsphere cells (13).…”
Section: Introductionmentioning
confidence: 99%